2018
DOI: 10.1080/09540121.2018.1469723
|View full text |Cite
|
Sign up to set email alerts
|

Patient activation among people living with HIV: a cross-sectional comparative analysis with people living with diabetes mellitus

Abstract: Standardized self-management supports are an integral part of care delivery for many chronic conditions. We used the validated Patient Activation Measure (PAM®) to assess level of engagement for self-management from a sample of 165 people living with HIV (PLWH) and 163 people with diabetes. We conducted multivariable logistic regression to assess associations between demographics and PAM® scores. PLWH had high levels of activation that were no different from those of people with diabetes (mean score = 67.2, SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
1
1
Order By: Relevance
“…In this study, patient activation status was found to be different from that reported in previous studies. The level of PAM in Yi minority PLWH is much lower than in studies conducted in Western countries, such as the United States (13) and Canada (17). It is concerning that more than 90% of our sample have Level 1 PAM scores.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In this study, patient activation status was found to be different from that reported in previous studies. The level of PAM in Yi minority PLWH is much lower than in studies conducted in Western countries, such as the United States (13) and Canada (17). It is concerning that more than 90% of our sample have Level 1 PAM scores.…”
Section: Discussioncontrasting
confidence: 65%
“…The PAM raw score was 29.8 ± 4.1 with a range of 14–45 (corresponding to the transformed score: 39.3 ± 6.0). A comparison of results from this study and previous studies ( 13 , 17 , 27 ) is shown in Figure 1 . In terms of patient activation level, the percentage of participants in Level 1 was as high as 97.8% ( n = 394); the percentage of patients in Level 2 and Level 3 were 1.7% ( n = 7) and 0.5% ( n = 2), respectively.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Com a disponibilidade de TARV, o HIV tornou-se uma infecção crônica que requer gestão por parte dos órgãos de saúde ao longo do tempo 16 . Dada a esta situação a prevenção é fundamental, e estratégias devem ser reavaliadas por parte da saúde pública.…”
Section: Discussionunclassified
“…The Patient Activation Measure (PAM), developed by Hibbard et al, offers a validated instrument to assess patient activation (Hibbard et al, 2005). Yet, few studies have examined patient activation among PLWH (Fiscella et al, 2015; Kendall et al, 2018; Marshall et al, 2013) and, to our knowledge, none have examined patient activation among Black women living with HIV (WLWH).…”
mentioning
confidence: 99%